The effect of a strategy training on reading comprehension in fourth-grade students. Issue 6 (2nd November 2018) - Muijselaar, Marloes; Swart, Nicole; Steenbeek-Planting, Esther; Droop, Mienke; Verhoeven, Ludo; de Jong, Peter
ABSTRACT: Previous studies have shown that instruction of reading strategies is an effective method for enhancing reading comprehension. However, many of the interventions in these studies focused on small groups of (poor) comprehenders and were provided by research assistants, making it time-consuming and relatively expensive. The authors implemented a strategy intervention to intact classrooms, consisting of reciprocal teaching and delivered by teachers. Participants were 510 typically developing fourth-grade students. A clustered randomized controlled trial was conducted with pretest, posttest, and follow-up measures to assess knowledge of reading strategies and reading comprehension. The results revealed that the intervention had an effect on knowledge of reading strategies at posttest and follow-up. However, the intervention did not affect reading comprehension performance. Together with the results of earlier studies, the present study raises the question whether strategy interventions are the most efficient to improve fourth-grade students' reading comprehension.